2018
DOI: 10.1016/j.prostaglandins.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

An inhibitor of soluble epoxide hydrolase ameliorates diabetes-induced learning and memory impairment in rats

Abstract: Inhibition of the sEH alleviates diabetes-induced decline in learning and memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 56 publications
(61 reference statements)
2
25
1
Order By: Relevance
“…It was found that a soluble epoxide hydrolase inhibitor (sEHI) alleviates transmissible spongiform encephalopathies (TSEs) associated with neuronal loss and inflammation (Poli et al, 2013). Earlier, we demonstrated that the sEHI, TPPU, minimizes memory impairment in diabetic rats (Minaz et al, 2018). These lines of research suggest that sEHIs may have potential therapeutic effect in managing AD associated memory impairment.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…It was found that a soluble epoxide hydrolase inhibitor (sEHI) alleviates transmissible spongiform encephalopathies (TSEs) associated with neuronal loss and inflammation (Poli et al, 2013). Earlier, we demonstrated that the sEHI, TPPU, minimizes memory impairment in diabetic rats (Minaz et al, 2018). These lines of research suggest that sEHIs may have potential therapeutic effect in managing AD associated memory impairment.…”
Section: Introductionmentioning
confidence: 77%
“…Diabetic rats were administered edaravone/EDV (3 mg/kg), edaravone (10 mg/kg), TPPU (1 mg/kg) or TPPU + DHA (100 mg/kg). The dose of TPPU was selected based on our previous studies on anti-inflammatory and memory protective activity of the enzyme inhibitor (Goswami et al, 2016; Minaz et al, 2018). Epoxy fatty acids generated from DHA were more stable and potent in the presence of the sEHI.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This mechanism – disrupting endothelial cell junctions of the BRB by sEH-dependent production of 19,20-DHDP – is worth investigating further since defects in the BRB contribute to other eye diseases (Campochiaro et al, 1999; Green, 1999). Furthermore, a recent study reported that sEH inhibitor TPPU reduces fasting glucose level in rats (Minaz et al, 2018). Given this, the antihyperglycemic effect of sEH inhibitors in relation to diabetic retinopathy is also worth exploring.…”
Section: Non-proliferative Diabetic Retinopathymentioning
confidence: 99%